Assistive Technology and Education Laboratory for Individuals with Visual Disabilities (GETEM) - Kanık, Leyla (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
This study, in general, deals with the information access for  individuals with visual disabilities (IVDs) in Turkey, and  the present situation of the information services provided for IVDs under the legal arrangements. In addition to these two issues, GETEM (Boğaziçi University Individuals with Visual Disabilities Technology Laboratory) project which was awarded  in terms of accessibility, and the stages of the project are examined. The Internet Library Project designed by GETEM aims to provide access to information services for IVDs. This project also includes individuals with other disabilities (e.g. paralysis, dyslexia) who cannot benefit from printed resources along with approximately 400 thousand IVDs. The library will mainly consist of Turkish and English resources. These resources will be story, novel, and poem genres, the course materials (e.g. books, articles, course notes, lecture records) the Turkish universities provide as well as academic articles/books. The texts of  online daily newspapers and weekly/monthly periodicals, and the  international libraries which offer services for IVDs will be accessible for IVDs. In this study, descriptive method is used. The research data is gathered by a review of literature, and by the interviews of GETEM executives.